ENERGETICS IN AGRICULTURE: CULTURAL PATTERN AS A STUMBLING BLOCK OR TAILWIND - Lečić, Rajna; Nikolić, Slavka (Journal on Processing and Energy in Agriculture, 2021)
Observed in the last decade, Serbia cannot boast of a high level of competitiveness, whereby the determined values of the innovation and business sophistication factors indicate that Serbia, in this subindex of competitiveness, noticeably lags behind even the EU countries with the lowest values of this indicator. Holding the attitude that sustainable development is a synergistic effect and a common denominator of energetics, agriculture and ecology, and the state of resources related to energetics and agriculture in Serbia is noticeably better than their effectiveness, we will introduce culture into the development equation and try to see the reasons for this situation through the prism of the prevailing cultural pattern of Serbia. Competitiveness as a key assumption for improving well-being of any country and considering the way of its improvement is the main goal of this work.
Keywords: cultural pattern; energetics in agriculture; competitiveness; effectiveness